1996
DOI: 10.1097/00007890-199604150-00018
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Cell Cluster Hypothesis for Noncognate T-B Collaboration via Direct T Cell Recognition of Allogeneic Dendritic Cells1

Abstract: In this article, we propose that T cell help for B cells can occur via an unusual three-cell cluster, with recipient CD4+ T helper cells interacting via direct allorecognition with donor dendritic cell class II MHC antigens, recipient B cells interacting with MHC class I (or any other) antigen on the donor dendritic cell surface, and noncognate (i.e., antigen nonspecific) T-B collaboration. In this noncognate pathway, antigen processing by B cells is not required and T cell help is potent because of the high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This ‘three-cell cluster model’ (Fig. 1 B ) was first suggested by Fabre, who noted that blockade of donor MHC class II alloantigen abrogated anti-MHC class I alloantibody responses to a rat heart graft (19).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…This ‘three-cell cluster model’ (Fig. 1 B ) was first suggested by Fabre, who noted that blockade of donor MHC class II alloantigen abrogated anti-MHC class I alloantibody responses to a rat heart graft (19).…”
Section: Introductionmentioning
confidence: 76%
“…Although previous publications, including our own, have concluded that direct-pathway CD4 T cells cannot provide help for class-switched alloantibody responses (18, 31, 63), we felt it important to re-examine this concept, because as discussed in the introduction and as suggested by Fabre’s findings (19, 64), these studies may obscure a role for direct-pathway help either because the B cell compartment lacked MHC class II expression (18) or because non-vascularised skin graft models were studied (31). Of more significance, definitive rebuttal of direct-pathway help for alloantibody production requires specific examination of the memory CD4 T cell subset.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the direct pathway, which is unique to transplantation, alloantigen is recognised intact on the surface of donor APCs, whereas in the indirect pathway, alloantigen is processed and presented as peptide fragments by recipient APCs for self-restricted recognition. One study has suggested that alloreactive B cells can receive help from direct-pathway CD4 T cells (15), but this has remained controversial (16), and we have demonstrated recently that only indirect-pathway CD4 T cells act as T follicular helper (T FH ) cells for generating long-lasting, class-switched alloantibody (17).…”
Section: Introductionmentioning
confidence: 99%